2020
DOI: 10.1111/os.12663
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and Safety of Cervical Kinematic Magnetic Resonance Imaging in Patients with Cervical Spinal Cord Injury without Fracture and Dislocation

Abstract: Objective: To evaluate the feasibility and safety of cervical kinematic MRI (KMRI) in patients with cervical spinal cord injury without fracture and dislocation (CSCIWFD).Methods: This was a single-institution case-only study. Patients with CSCIWFD were enrolled in our institution from February 2015 to July 2019. Cervical radiography and CT were performed first to exclude cervical tumors, and major fracture or dislocation. Then neutral static and kinematic (flexion and extension) MRI was performed for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In addition, one study also reported improved sensitivity of STIR over T2w images (82% vs. 61%) to identify intervertebral disc injury/herniation [ 18 ]. Two studies found 2 and 5 cases, respectively, of acute disc herniation on MRI that were verified by intraoperative findings [ 22 , 23 ]. Another study investigated the diagnostic accuracy of T2w images to detect intramedullary hemorrhage/contusion/edema in patients with SCIWORA compared with direct visualization of the spinal cord, reporting a sensitivity of 100% [ 19 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, one study also reported improved sensitivity of STIR over T2w images (82% vs. 61%) to identify intervertebral disc injury/herniation [ 18 ]. Two studies found 2 and 5 cases, respectively, of acute disc herniation on MRI that were verified by intraoperative findings [ 22 , 23 ]. Another study investigated the diagnostic accuracy of T2w images to detect intramedullary hemorrhage/contusion/edema in patients with SCIWORA compared with direct visualization of the spinal cord, reporting a sensitivity of 100% [ 19 ].…”
Section: Resultsmentioning
confidence: 96%
“…Seven studies involving SCI were identified that addressed KQ1 ( Table 3 ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Five studies calculated the diagnostic accuracy of MRI in relation to intraoperative findings [ 17 , 18 , 19 , 22 , 23 ], one compared against flexion/extension radiographs [ 20 ], and one against CT myelography [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bao et al analyzed the safety of kMRI in 16 patients with spinal cord injury and found that it had greater advantages than the neutral position MRI. 11 Nevertheless, as far as we know, no study has evaluated the characteristics of TCCS using kMRI and whether it can be used to identify prognostic factors of TCCS. The current study therefore aimed to assess the characteristics of DSCI by kMRI and to evaluate the risk factors for poor outcomes in patients with TCCS after surgery.…”
Section: Introductionmentioning
confidence: 99%